Induction of Protective Immunity against Streptococcus mutans Colonization after Mucosal Immunization with Attenuated Salmonella enterica Serovar Typhimurium Expressing an S. mutans Adhesin under the Control of In Vivo-Inducible nirB Promoter - Huang, Yan (American Society for Microbiology, 2001)
The purpose of the present study was to evaluate the effectiveness of an attenuated Salmonella enterica serovar Typhimurium vaccine strain expressing the saliva-binding region (SBR) of the Streptococcus mutans antigen I/II adhesin, either alone or linked with the mucosal adjuvant cholera toxin A2 and B subunits (CTA2/B) and under the control of the anaerobically inducible nirB promoter, in inducing a protective immune response against S. mutans infection. BALB/c mice were immunized by either the intranasal or the intragastric route with a single dose of 10(9) or 10(10) Salmonella CFU, respectively. The Salmonella vaccine strain expressing an unrelated antigen (fragment C of tetanus toxin [TetC]) was also used for immunization as a control. Samples of serum and secretion (saliva and vaginal washes) were collected prior to and following immunization and assessed for antibody activity by enzyme-linked immunosorbent assay. Anti-SBR antibodies were detected in the serum and saliva of experimental animals by week 3 after immunization. A booster immunization at week 17 after the initial immunization resulted in enhanced immune responses to the SBR. The serum immunoglobulin G subclass profiles were indicative of T helper type 1 responses against both the vector and the SBR antigen. To determine the effectiveness of these responses on the protection against S. mutans infection, mice were challenged after the second immunization with a virulent strain of S. mutans which was resistant to tetracycline and erythromycin. Prior to the challenge, mice were treated for 5 days with tetracycline, erythromycin, and penicillin. S. mutans was initially recovered from all of the challenged mice. This bacterium persisted at high levels for at least 5 weeks in control TetC-immunized or nonimmunized mice despite the reappearance of indigenous oral organisms. However, mice immunized with Salmonella clones expressing SBR or SBR-CTA2/B demonstrated a significant reduction in the number of S. mutans present in plaque compared to the control groups. These results provide evidence for the effectiveness of the Salmonella vector in delivering the SBR antigen for the induction of mucosal and systemic immune responses to SBR. Furthermore, the induction of a salivary anti-SBR response corresponded with protection against S. mutans colonization of tooth surfaces.